Inefficient Metabolism of the Human Milk Oligosaccharides Lacto-N-tetraose and Lacto-N-neotetraose Shifts Bifidobacterium longum subsp. infantis Physiology - Özcan, Ezgi; Sela, David A. (Frontiers in Nutrition, 2018)
Breast milk contains a high concentration of indigestible oligosaccharides, which likely mediated the coevolution of the nursing infant with its gut microbiome. Specifically, Bifidobacterium longum subsp. infantis (B. infantis) often colonizes the infant gut and utilizes these human milk oligosaccharides (HMO) to enrich their abundance. In this study, the physiology and mechanisms underlying B. infantis utilization of two HMO isomers lacto-N-tetraose (LNT) and lacto-N-neotetraose (LNnT) was investigated in addition to their carbohydrate constituents. Both LNT and LNnT utilization induced a significant shift in the ratio of secreted acetate to lactate (1.7-2.0) in contrast to the catabolism of their component carbohydrates (~1.5). Inefficient metabolism of LNnT prompts B. infantis to shunt carbon towards formic acid and ethanol secretion. The global transcriptome presents genomic features differentially expressed to catabolize these two HMO species that vary by a single glycosidic linkage. Furthermore, a measure of strain-level variation exists between B. infantis isolates. Regardless of strain, inefficient HMO metabolism induces the metabolic shift towards formic acid and ethanol production. Thus differential metabolism of milk glycans potentially drives the emergent physiology of host-microbial interactions to impact infant health.